2015
DOI: 10.1134/s0006297915050132
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric examination of mitochondrial ultrastructure in aging cardiomyocytes

Abstract: Mitochondrial ultrastructure in cardiomyocytes from 3- and 24-month-old Wistar and OXYS rats was investigated using a new approach designed for morphometric analysis. The data fully confirm the electron microscopy data: the area of the inner mitochondrial membrane per unit volume of mitochondria was significantly decreased with age, as found on heart muscle section. In 3-month-old Wistar rats from the control group, this parameter was 41.3 ± 1.52 µm(2)/µm(3), whereas in OXYS rats it was decreased to 30.57 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 24 publications
(9 reference statements)
5
24
1
2
Order By: Relevance
“…For morphometric analysis of mitochondrial ultrastructure and of the average area of one mitochondrial section in the lacrimal gland, the Adobe ® Photoshop ® graphics editor was used for direct calculations, as described elsewhere [36-37]. …”
Section: Methodsmentioning
confidence: 99%
“…For morphometric analysis of mitochondrial ultrastructure and of the average area of one mitochondrial section in the lacrimal gland, the Adobe ® Photoshop ® graphics editor was used for direct calculations, as described elsewhere [36-37]. …”
Section: Methodsmentioning
confidence: 99%
“…Whereas some studies demonstrate a reduced number of mitochondria in the cytosol of aged cardiomyocytes, others show that the mitochondrial volume fraction is unaltered during ageing . Mitochondrial shape is altered with increasing age (less elongated and more round), and the area of the mitochondrial inner membrane per mitochondrion is reduced in aged myocardium although cristae configuration is not affected …”
Section: Age‐associated Changes In the Heartmentioning
confidence: 98%
“…Evidence suggests that the mitochondria structure is disrupted in cardiac senescence, with increased mitochondria size [34]. Electron-microscopy-based studies have demonstrated that the area of IMM obviously decreases [35], showing a loss of cristae with age in rodent heart [36]. Mitochondrial dynamics have been involved in the aging process [37], and the promotion of fusion or blockade of fission prompts cell senescence [17].…”
Section: Mitochondrial Dysfunction In Cardiac Agingmentioning
confidence: 99%